Proficiency Level and Challenges of Grade 11 Public School Students on Contemporary Issues - Maria Arvelyn Rios; Joel M. Bual; Dennis V. Madrigal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Contemporary issues is essential for K-12 learners to develop their awareness of the social conditions as potential problem solvers. Hence, proficiency assessment is necessary to check their competency acquisition. This study aims to analyze the Grade 10 students’ proficiency and challenges on contemporary issues among public schools in Central Philippines in the importance of studying contemporary issues, political rights, human rights, and educational rights relative to sex and strand. Utilizing a descriptive-comparative approach, a validated and reliability tested questionnaire and checklist were administered to 261 students using beginning, developing, approaching proficiency, proficiency, and advanced responses. In data analysis, mean, standard deviation, frequency count, percentage, rank, Mann Whitney, and Kruskal Wallis were employed. Generally, they have approaching proficiency in all areas indicating that the competencies were not fully acquired. With this, improvement on instruction is critical. Comparatively, there was a difference when grouped to sex and strand where females and TVL students rated higher proficiency than their counterparts. Meanwhile, they are challenged on their motivation to learn, traditional teaching strategies, time management in accomplishing tasks, inadequate learning facilities, and insufficient interactive learning opportunities. Given the results, these imply the importance of improving the teachers’ instructional strategies in ensuring the students’ quality proficiency in Contemporary issues.